Benefits of Psychological Androgyny in Adolescence: The Role of Gender Role Self-Concept in School-Related Well-Being - Korlat, Selma; Holzer, Julia; Schultes, Marie-Therese; Buerger, Sarah; Schober, Barbara; Spiel, Christiane; Kollmayer, Marlene (Frontiers in Psychology, 2022)
It has been repeatedly shown that the extent to which individuals adopt stereotypically masculine and feminine traits in their self-concept impacts their health and well-being. This is especially important in adolescence, when developmental changes and social pressures to conform to stereotypical gender roles can affect psychological functioning. However, previous studies investigating gender role self-concept and well-being with adolescents focused mostly on general well-being rather than well-being in specific contexts. Given that school is one of the most important contexts for adolescents' development and well-being, the aim of this study was to investigate differences between adolescents with different gender role self-concepts (masculine, feminine, androgynous and undifferentiated) in school-related well-being. In line with the new conceptualization of well-being uniting hedonic (pleasure attainment and pain avoidance) and eudemonic (self-actualization and having meaningful purpose in one’s life) approaches, the present study used a measure of school-related well-being encompassing the five domains suggested in the EPOCH (Engagement, Perseverance, Optimism, Connectedness and Happiness) model as well as a superordinate well-being factor. A total of 999 Austrian adolescents (52.2% girls, Mage = 13.79, SDage = 1.53) answered inventories assessing adolescents’ gender role self-concept (GRI-JUG) and school-related well-being (EPOCH-G-S). The results supported the androgyny model of well-being, showing clear advantages of having both positive masculine and feminine qualities in one’s self-concept for optimal levels of school-related well-being. In addition, our results indicated the strong importance of femininity in adolescence and the school context. Theoretical and practical implications are discussed.